Toward Integrated Multi-Omics Intervention: Rice Trait Improvement and Stress Management - Iqbal, Zahra; Iqbal, Mohammed Shariq; Khan, M. Iqbal R.; Ansari, Mohammad Israil (Frontiers in Plant Science, 2021)
Rice (Oryza sativa) is an imperative staple crop for nearly 60% of the world’s population. Challenging environmental conditions encompassing abiotic and biotic stresses negatively impact the quality and yield of rice. To assure food supply for the unprecedented ever-growing world population, the improvement of rice as a crop is of utmost importance. In the post-genomic era, “omics” techniques have been comprehensively utilized to decipher the regulatory mechanisms and cellular convolutions in rice. Recent omics advances have provided a solid platform for scrupulous exploration of genetic resources involved in the rice trait development. Omics techniques like genomics, transcriptomics, proteomics, and metabolomics have significantly contributed towards the achievement of desired improvements in rice cultivars. The present review recapitulates the basic and applied multi-omics technologies in providing new orchestration towards improvement of rice quantitative and qualitative traits. The article also provides a catalog of current scenario of omic applications in comprehending this imperative crop in relation to yield enhancement and various environmental stresses. Further, the appropriate databases in the field of data sciences to analyse big data and retrieve relevant information vis-à-vis rice trait improvement and stress management are described.